Characterization of Staphylococcus aureus isolated from chicken and quail eggshell (Journal of Advanced Veterinary and Animal Research, 2018)
Objectives: This study was conducted to assess the prevalence and characterization of Staphylococcus aureus from chicken and quail eggshells and to study the antibiogram of the isolates.Materials and methods: A total of 300 eggs (220 chicken eggs and 80 quail eggs) were collected from different retail shops and farms in Mymensingh district. Swabs taken from the egg surfaces were cultured on Mannitol Salt Agar for the isolation of S. aureus. Polymerase chain reaction was conducted for confirmatory identification of the bacterial species targeting nuc gene, followed by confirmation of methicillin-resistant S. aureus by targeting the mecA gene. Antibiotic sensitivity test of the isolated bacteria was done against commonly used antibiotics by the disk diffusion method.Results: The prevalence of Staphylococcus spp. and S. aureus in the chicken eggshell surface was 20.45% and 10.45%, respectively. Similarly, the prevalence of Staphylococcus spp. and S. aureus in quail eggshell surface was 16.25% and 5%, respectively. Overall, 27 isolates were identified as S. aureus, of which 23 were from the chicken eggshell surface and four from quail eggshell surface. Among the seven isolates tested, overall four (57.14%) were positive for the nuc gene. On the other hand, the mecA gene could be detected in three (50%) S. aureus out of six oxacillin resistant isolates. The antibiogram study indicated that most of the isolates were resistant to the antibiotics under β-lactam group.Conclusion: The present study concludes that chicken and quail egg surface harbor multidrug- resistant bacteria which may cause public health hazards, if these antibiotic-resistant bacteria are transferred to a human.http://doi.org/10.5455/javar.2018.e300